2018
DOI: 10.1007/s00701-017-3438-z
|View full text |Cite
|
Sign up to set email alerts
|

Gross total resection of pituitary adenomas after endoscopic vs. microscopic transsphenoidal surgery: a meta-analysis

Abstract: Among patients who were not randomly allocated to either approach, eTSS resulted in a higher rate of GTR as compared to mTSS for all patients and for NFPA patients alone, but only in a fixed-effect model. For FPA, however, eTSS did not seem to offer a significantly higher rate of GTR. These conclusions should be interpreted with caution because of the nature of the included non-comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 85 publications
1
57
1
2
Order By: Relevance
“…Following deduplication and abstract review, 51 relevant articles were identified. Thereafter remained fourteen primary papers [ 8 , 17 , 20 , 26 , 33 , 34 , 37 , 39 , 46 , 51 , 55 , 58 – 60 ], and 37 secondary papers [ 1 5 , 9 12 , 14 16 , 23 , 27 , 29 32 , 35 , 36 , 38 , 40 , 43 45 , 47 50 , 52 54 , 57 , 62 , 64 – 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following deduplication and abstract review, 51 relevant articles were identified. Thereafter remained fourteen primary papers [ 8 , 17 , 20 , 26 , 33 , 34 , 37 , 39 , 46 , 51 , 55 , 58 – 60 ], and 37 secondary papers [ 1 5 , 9 12 , 14 16 , 23 , 27 , 29 32 , 35 , 36 , 38 , 40 , 43 45 , 47 50 , 52 54 , 57 , 62 , 64 – 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Of them, 13 (35%) were narrative reviews [ 9 , 11 , 15 , 27 , 29 31 , 43 45 , 52 , 53 , 64 ]. Eleven (30%) were systematic reviews [ 1 , 5 , 10 , 14 , 16 , 38 , 40 , 46 , 48 , 49 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pituitary adenomas are the most frequently studied and managed endoscopically. A 2018 metanalysis of 50 studies by Almutairi et al 47 demonstrated a GTR rate for pituitary adenomas of 74%. For tumors invading the cavernous sinus, many authors noted a higher resection rate with an endoscope than a microscope, indicating the advantage of the panoramic and angled views of the medial wall of the cavernous sinus provided by endoscopes.…”
Section: Extent Of Resectionmentioning
confidence: 99%
“…The modification of the surgical technique in our center was previous analyzed and the authors concluded that the two techniques were similar in terms of surgical safety [12]. In addition, in a recent meta-analysis, endoscopic surgery did not show a significantly higher rate in terms of gross total tumor resection in comparison to microscopic surgery for functioning pituitary adenomas [13]. The goal of the neurosurgical team for the first TSS was adenomectomy, hemi-hypophysectomy or total hypophysectomy being reserved for cases that required surgical reintervention.…”
Section: Methodsmentioning
confidence: 99%